Fast electrical potentials arising from activation of metarhodopsin in the fly (The Rockefeller University Press, 1980)
The cellular origin and properties of fast electrical potentials arising from activation of Calliphora photopigment were investigated. It was found by intracellular recordings that only the corneal-negative M1 phase of fly M potential arises in the photoreceptors' membrane. This M1 phase has all the accepted characteristics of an early receptor potential (ERP). It has no detectable latency, it survives fixation with glutaraldehyde, it is linear with light intensity below pigment saturation, and it is linear with the amount of metarhodopsin activated by light. The Calliphora ERP was found, however, to be exceptional because activation of rhodopsin, which causes the formation of metarhodopsin in 125 microsecond (25 degrees C), was not manifested in the ERP. Also, the extracellularly recorded ERP was not proportional to the rate of photopigment conversion. The corneal-positive M2 phase of the M potential was found to arise from second-order lamina neurons (L neurons). Intracellular recordings from these cells showed a fast hyperpolarizing potential, which preceded the normal hyperpolarizing transient of these cells. This fast potential appeared only when metarhodopsin was activated by a strong flash. The data indicate that the intracellularly recorded positive ERP, which arises from activation of metarhodoposin, elicits a hyperpolarizing fast potential in the second-order neuron. This potential is most likely the source of the corneal-positive M potential.